THE EFFECTIVENESS OF EXPERIENTIAL LEARNING METHODS IN IMPROVING THE LEARNING QUALITY OF CHRISTIAN RELIGIOUS EDUCATION TEACHERS - Itje, Tomi; Hohakay, Karwanto Oktofianus; Tasiringan, Marton; Djanti, Riko; Labaka, Sesar (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The quality of Christian Religious Education learning in remote areas still faces challenges, especially related to the limitations of pedagogic competence and the lack of innovation in learning methods. This study aims to analyze the effectiveness of experiential learning  methods in improving the learning quality of Christian Religious Education teachers at SATAP Kusuri State Junior High School, North Halmahera. This study uses the Mixed Methods Research approach, which combines quantitative and qualitative approaches in one study to obtain a more comprehensive understanding. The subjects of the study include Christian education teachers, and students. Data was collected through observation, interviews, and surveys, then analyzed using interactive analysis techniques that included data reduction, data presentation, and conclusion drawing through triangulation. The results of the study show that the application  of experiential learning  methods is effective in improving the quality of learning, shown by the achievement of all indicators, there is an average score of 89% with the very good category. This method has been proven to increase student involvement, reflective thinking skills, and the application of concepts in real contexts. However, limited access to teacher professional training is the main obstacle in optimizing learning. Therefore, it is necessary to strengthen teacher capacity through practice-based continuous training as a strategy to improve the quality of learning in remote areas.